If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -5 + -1x = -7 Combine like terms: 4 + -5 = -1 -1 + -1x = -7 Solving -1 + -1x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = -7 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = -7 + 1 -1x = -7 + 1 Combine like terms: -7 + 1 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 2a+8b+3a-2b= | | 3m-5+7m+12=87 | | (x+1)^2/3=4 | | -11/-8=x*2/1 | | 2/x=(3/x-2)-1 | | 1/7(5x+62)=11 | | 15*8x=11+6x | | (-2/9)(-3x)(-6) | | 4d-4=6d+10 | | 2(c-6)+-9=-3 | | 12/2=x | | 20/4/5 | | 4n=-16 | | 7m=21 | | 4a/5=20 | | 3(5x+6)=153 | | 4/s=2 | | 249-6x=183 | | 6/p=-2 | | -2(4s-3)-6=2(6s+3)-2 | | 3(4-2x)=18 | | 7-g=4 | | x-10-5=-14 | | 16+2l+l=73 | | 3u-15=36 | | m+9=4 | | 8=2(t+2) | | (C-4)+(3c+9)= | | -8=24+y | | 8=2(v+3) | | x*x*x*x=20 | | -2(3s-6)-12=-3(5s+-1)-5 |